Answers

2016-02-20T12:40:58+05:30
Ok, let me try
✨(x-2)/(x-4)+(x-6)/(x-8)=20/3
(x-2)(x-8)(3)+(x-6)(x-4)(3)=20(x-4)(x-8)
(3)(x²-8x-2x+16)+(3)(x²-4x-6x+24)=20(x²-8x-4x+48)
3x²-24x-6x+48+3x²-12x-18x+72=20x²-160x-80x+960
6x²-60x+120=20x²-240x+960
0=20x²-6x²-240x+60x+960-120
0=14x²-180x+840
0=x²-12x+60 [because 14≠0]

That's it! You've got the equation. you'll get the value of x by solving it. hope it helped. ^_^
1 5 1
but , (x-4)(x-8) = x^2 - 12x + 32
yes, but I didn't add those 
I multiplied them with 20
adn then I added them
*and, not adn